Effectiveness of sofosbuvir-based treatments for patients with hepatitis C virus genotype 6 infection: a real-world study from East China - Jiang, Fan-Rong; Ye, Xiao-Ting; Huang, He-Qing; Hu, Yu-Tao; Wang, Dong-Hui; Jiang, Su-Wen; Wang, Jia-Lan; Hu, Ai-Rong (Frontiers in Medicine, 2024)
Background Over the past decade, the proportion of hepatitis C virus (HCV) genotypes (GT) 1 and 2 has decreased in almost all regions of China, while GT 3 and 6 have emerged as new challenges. GT 6 is unique in many respects, like high genetic variability and emerging resistant variants. This study aims to assess the efficacy of sofosbuvir (SOF)-based treatments in patients with GT 6 chronic hepatitis C (CHC). Methods A retrospective analysis was conducted on patients with GT 6 HCV infection, who were diagnosed between July 2018 and May 2023. All patients received a 12-week course of SOF-based treatments. The primary efficacy endpoint was sustained virologic response (SVR), which is defined as having undetectable HCV RNA at 12 weeks after treatment completion (SVR12). The efficacy data for SVR12 were analyzed using both the evaluated population (EP) and per-protocol population (PP). For the PP populations, efficacy data were stratified using Forrester plots. Results A total of 201 patients were included in the study. In PP population, the end of treatment virological response rate was 99.48% (190/191), the SVR12 rate was 99.31% (143/144), and the SVR24 rate was 100.00% (75/75). Only one patient with genotype 6a experienced a relapse 12 weeks after the completion of treatment, but her HCV RNA was undetectable both at the end of treatment and 24 weeks after the end of treatment. Additionally, the normalization rates of alanine transaminase (ALT) and aspartate aminotransferase (AST) were significantly higher at the end of treatment (EOT) compared to baseline (27.36% vs. 93.03%, 36.32% vs. 95.02%, p < 0.001). Significant improvements were observed in the levels of total bilirubin, ALT, AST, albumin, globulin, albumin/globulin ratio, gamma-glutamyl transferase, alkaline phosphatase, platelet, fibrosis-4 (FIB-4), and aspartate transaminase to platelet ratio index (APRI) between baseline and EOT (p < 0.05). Conclusion SOF-based treatments achieved high virological and biochemical response rates in patients with HCV GT 6 infection.